Maximizing Integrated Optical and Electrical Properties of a Single ZnO Nanowire through Native Interfacial Doping. (22nd January 2014) - Ding, Huaiyi; Pan, Nan; Ma, Chao; Wu, Yukun; Li, Junwen; Cai, Hongbing; Zhang, Kun; Zhang, Guanghui; Ren, Wenzhen; Li, Jianqi; Luo, Yi; Wang, Xiaoping; et al.
<x xml:space="preserve">Abstract</x> A native interfacial doping layer introduced in core–shell type ZnO nanowires by a simple vapor phase re‐growth procedure endows the produced nanowires with both excellent electrical and optical performances compared to conventional homogeneous ZnO nanowires. The unique Zn‐rich interfacial structure in the core–shell nanowires plays a crucial role in the outstanding performances. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>